Effect of hip-shoulder and shoulder-arm separations on discus throwing performance - Leigh, S.; Bing Yu (ISBS - Conference Proceedings Archive (Konstanz), 2005)
The purpose of this study was to analyze performances of nationally competitive discus throwers to ascertain which launch phase technique variables have the most influence on release characteristics and official distance. Three-dimensional videography was used to analyze 259 trials. The angles in the horizontal plane between the line of the athlete's hips, shoulders, and throwing arm, at six critical instants of the launch phase were calculated and analyzed. Our data suggests females utilize effective body positions throughout more of the launch phase to maximize the distance thrown. In contrast, males rely mainly on their upper extremity strength to achieve comparable results.